Correlation between Hearing Loss with Acute Encephalitis Syndrome in Indonesian Children - Gunawan, Prastiya Indra; Polanunu, Masayu Ramadhani (Journal of Liaquat University of Medical & Health Sciences, 2023)
OBJECTIVE: The study aimed to correlate hearing loss and clinical characteristics in children following Acute Encephalitis Syndrome. METHODOLOGY: This cross-sectional study was conducted in the pediatric neurology outpatient clinic and audiology outpatient clinic of Dr. Soetomo Hospital Surabaya from August 2018 to January 2019. Written informed consent was obtained from parents before the study. Cases of AES with ages three months to 18 years were included. Age, fever, seizures, decreased consciousness and brain edema were analyzed. Hearing loss was evaluated by using Otoport Automated Auditory Brainstem Response (ABR). Statistical analysis was done by using the Fisher Exact test. RESULTS: A total of 25 children were enrolled in the study, 60 % male and 52% aged < 12 months. There was a diagnosis of meningoencephalitis in 52% of patients, and hearing loss occurred in 5 patients. Age, fever, seizure, decreased consciousness and brain edema were evaluated as clinical characteristics of hearing loss. Fever > 39°C (p = 0,046), seizure ? 30 minutes (p = 0,038) and decreased consciousness (Glasglow Coma Scale (GCS) ? 8) (p = 0.002) were significantly correlated with hearing loss in AES. CONCLUSION: Fever, seizure and decreased consciousness correlated with hearing loss in children with AES.